The effect of bovine colostrum supplementation on exercise performance in elite field hockey players - Hofman, Z.; Smeets, R.; Verlaan, G.; van der. Lugt, R.; Verstappen, P. A. (International Journal of Sport Nutrition and Exercise Metabolism, 2002)
In a double-blind, randomized, placebo-controlled study, we investigated the effect of 8 weeks of supplementation with bovine colostrum (Intactª) on body composition and exercise performance (5 3 10-m sprint, vertical jump, shuttle-run test, and suicide test). Seventeen female and 18 male elite field hockey players, including players from the Dutch national team, received either 60 g of colostrum or whey protein daily. The 5 3 10-m sprint test performance improved significantly (p = .023) more in the colostrum group [0.64 ± 0.09 s (mean ± SEM)] compared to the whey group (0.33 ± 0.09 s). The vertical jump performance improved more in the colostrum group (2.1 ± 0.73 cm) compared to the whey group (0.32 ± 0.82 cm). However, this was not statistically significant (p = .119). There were also no significant differences in changes in body composition and endurance tests between the 2 groups. It is concluded that in elite field hockey players, colostrum supplementation improves sprint performance better than whey. However, there were no differences with regard to body composition or endurance performance.